Learning Style Differences as an Issue in EFL Classroom - Bhandari, Harischandra (AWADHARANA, 2022)
This article explores the concepts on learners' learning style differences as an issue in EFL classroom. In a large and heterogeneous classroom, different learners have different learning styles due to their different nature, preferences, interests, attitudes, skills and ways of grasping knowledge about the world. Existence of differences in a classroom generally creates difficulty to the EFL teachers. I mainly reviewed and analyzed the documents consisting books, articles and reports of seven authors on the basis of five themes: learner differences, factors of learner differences, models of learning styles, aspects of classroom management and raising awareness. It was found that to deal with the students of learning style differences and managing classroom situations, raising awareness on the learning styles of teachers and students is essential. Recognizing students' and teachers' learning styles, knowledge of factors of learning style differences, familiarity on the concept of learning style differences and knowledge of the models of learning styles help the teachers to be well introduced with the issue and deal with the students in the classroom.